Catalyst, preparation method thereof and application of catalyst in catalyzing polystyrene pyrolysis
By loading transition metal elements on H-Beta or ZSM-5 molecular sieve, an efficient catalyst was prepared, which solved the problem of insufficient conversion efficiency and catalyst regenerability in polystyrene recovery, and achieved efficient and selective styrene conversion and good cycle stability of the catalyst.
Patent Information
- Application Number
- CN202411618825.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
In the prior art, when recycling polystyrene plastics, it is difficult to achieve efficient and highly selective conversion to styrene, and the regeneration and cycle stability of the catalyst is insufficient, which limits its reuse.
A catalyst precursor was prepared by using H-Beta or ZSM-5 molecular sieve as a support, supporting transition metal elements such as Cu, Zn, Co or Ni, and a catalyst with high catalytic efficiency was obtained by calcining and reducing treatment. The catalyst catalyzes the pyrolysis of polystyrene under relatively mild conditions (285-295°C) and has good cycle stability and universality.
It realizes the efficient and selective conversion of polystyrene to styrene, the catalyst is easy to regenerate, and has good cycle stability. It is suitable for the recycling of commercial waste polystyrene plastics and mixed plastics.
Smart Images

Figure CN119633892A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical catalysis, and in particular relates to a catalyst, a preparation method thereof and an application of the catalyst in catalyzing the thermal decomposition of polystyrene. Background Art
[0002] Polystyrene (PS) plastics are widely used in many fields, such as food packaging, medical and health care, and construction consumables, due to their mechanical durability and easy processability. Unfortunately, the accumulation of PS poses an ecological and economic threat, making it critical to develop chemical recycling methods to depolymerize and reuse PS waste.
[0003] Conventional PS depolymerization methods, such as pyrolysis and catalytic hydrogenation, often produce complex hydrocarbon mixtures that are difficult to separate, thus reducing their usability.
[0004]
[0005] Therefore, avoiding unwanted hydrocarbons in the target alkane or aromatic products is an important consideration for PS recovery. Researchers have developed new technologies for PS recovery, such as non-thermal plasma-assisted hydrogenolysis and photocatalytic decomposition at ambient temperature and atmospheric pressure, but the selectivity is still unsatisfactory. Therefore, it is still very challenging to explore efficient catalytic systems for the targeted conversion of polystyrene waste plastics into high-value chemicals. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a catalyst, a preparation method thereof and an application of catalyzing the pyrolysis of polystyrene. The catalyst can catalyze the pyrolysis of polystyrene under relatively mild conditions, so that it can be efficiently and selectively converted into styrene; the catalyst is easy to regenerate, has good cycle stability, and is conducive to repeated use; and it has universal applicability in the recycling of commercial waste polystyrene plastics and polystyrene mixed plastics.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a catalyst precursor, the catalyst precursor comprising a molecular sieve, and a transition metal element supported in the molecular sieve;
[0009] The molecular sieve is H-Beta molecular sieve and / or ZSM-5 molecular sieve;
[0010] The transition metal element is selected from one or more of Cu, Zn, Co and Ni, and the transition metal element exists in the form of oxide.
[0011] In some embodiments of the present invention, the loading amount of the transition metal element in the catalyst precursor is 0.1-1wt%, for example, it can be 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%, etc.; preferably 0.1-0.8wt%, more preferably 0.2wt%. However, the present invention is not limited to the listed values, and other values not listed in this range are also applicable.
[0012] In some embodiments of the present invention, the transition metal element is Co and / or Ni.
[0013] In some embodiments of the present invention, the molecular sieve is H-Beta molecular sieve.
[0014] In some embodiments of the present invention, the molar ratio of Si to Al in the molecular sieve is 10-13:1; for example, it can be 10:1, 10.2:1, 10.5:1, 10.8:1, 11:1, 11.2:1, 11.5:1, 11.8:1, 12:1, 12.2:1, 12.5:1, 12.8:1 or 13:1, etc. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0015] In a second aspect, the present invention provides a method for preparing the catalyst precursor as described in the first aspect, the preparation method comprising the following steps:
[0016] The aqueous solution of transition metal salt is mixed with molecular sieve, dried, and then calcined in an oxygen-containing atmosphere to decompose the transition metal salt to form oxides, thereby obtaining the catalyst precursor.
[0017] In some embodiments of the present invention, the transition metal salt is a nitrate of a transition metal. The nitrate of a transition metal is more easily decomposed to form a transition metal oxide when calcined in an oxygen-containing atmosphere.
[0018] In some embodiments of the present invention, the concentration of the transition metal element in the aqueous solution of the transition metal salt is 0.5-1 mol / L; for example, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0019] In some embodiments of the present invention, the mixing method is: dripping the aqueous solution of the transition metal salt onto the molecular sieve and stirring until the surface is dry; or, immersing the molecular sieve in the aqueous solution of the transition metal salt for a period of time and separating the solid.
[0020] In some embodiments of the present invention, the drying method is: drying at 100-120°C (for example, it can be 100°C, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C or 120°C, etc.).
[0021] As a non-limiting example, the oxygen-containing atmosphere in the present invention may be an air atmosphere, an oxygen atmosphere, or the like.
[0022] In some embodiments of the present invention, the calcination temperature is 450-650°C, for example, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C, 620°C or 650°C, etc. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0023] In some embodiments of the present invention, the calcination time is 4-8 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, etc. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0024] In a third aspect, the present invention provides a catalyst, comprising a molecular sieve, and a transition metal element supported in the molecular sieve;
[0025] The molecular sieve is H-Beta molecular sieve and / or ZSM-5 molecular sieve;
[0026] The transition metal element is selected from one or more of Cu, Zn, Co and Ni, and the transition metal element exists in the form of a metal element.
[0027] Molecular sieve is a kind of aluminosilicate crystal with regular pore structure, which is composed of [SiO4] and [AlO4] tetrahedrons through shared vertex oxygen atoms. Its chemical formula can be expressed as M n / m (SiO2)(AlO2) n ·xH2O (M is a cation, and the valence state is m). The pore structure of the molecular sieve makes it a carrier for loading transition metal elements.
[0028] The present invention selects appropriate molecular sieves and transition metal elements, and loads transition metals in molecular sieves, thereby obtaining a catalyst with good performance. The catalyst can catalyze the thermal decomposition of polystyrene under relatively mild conditions (285-295°C), so that it can be efficiently and selectively converted into styrene; the catalyst is easy to regenerate, has good cycle stability, and is conducive to repeated use; and it has universal applicability in the recovery of commercial waste polystyrene plastics and polystyrene mixed plastics.
[0029] In some embodiments of the present invention, the loading amount of the transition metal element in the catalyst is 0.1-1wt%, for example, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%, etc.; preferably 0.1-0.8wt%, more preferably 0.2wt%. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0030] In the present invention, the loading amount of the transition metal element is kept within the above range, which is helpful to obtain a catalyst with good performance, wherein when the loading amount of the transition metal element is 0.2wt%, the performance of the catalyst is the best. If the loading amount of the transition metal element is too low, there are fewer active centers in the catalyst, and the catalyst has a low catalytic pyrolysis efficiency for polystyrene; if the loading amount of the transition metal element is too high, the transition metal element will occupy more acid sites, which will also lead to a low catalytic pyrolysis efficiency for polystyrene.
[0031] In some embodiments of the present invention, the transition metal element is Co and / or Ni.
[0032] In some embodiments of the present invention, the molecular sieve is H-Beta molecular sieve.
[0033] In the present invention, when the transition metal element is Co and / or Ni and the molecular sieve is H-Beta molecular sieve, the obtained catalyst has higher catalytic efficiency.
[0034] The smaller the molar ratio of Si to Al in the molecular sieve, the more Al accounts for, the more acidic sites in the molecular sieve, and the stronger the catalytic activity; but when Al accounts for too much, the structure of the molecular sieve is unstable. Therefore, the molar ratio of Si to Al in the molecular sieve described in the present invention is preferably 10-13:1; for example, it can be 10:1, 10.2:1, 10.5:1, 10.8:1, 11:1, 11.2:1, 11.5:1, 11.8:1, 12:1, 12.2:1, 12.5:1, 12.8:1 or 13:1, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0035] In a fourth aspect, the present invention provides a method for preparing the catalyst according to the third aspect, the preparation method comprising the following steps:
[0036] The catalyst precursor described in the first aspect, or the catalyst precursor prepared by the preparation method described in the second aspect, is heated in a reducing atmosphere to react, so that the oxide of the transition metal element in the catalyst precursor is reduced to a metal element, thereby obtaining the catalyst.
[0037] It should be noted that since the catalyst provided by the present invention contains a transition metal element, the transition metal is easily reoxidized to an oxide in an air environment, so the catalyst needs to be stored in a non-oxidizing environment; or stored in the form of a catalyst precursor, and the catalyst precursor is prepared into a catalyst by the above method when used.
[0038] In some embodiments of the present invention, the reducing atmosphere is a hydrogen atmosphere.
[0039] In some embodiments of the present invention, the reaction temperature is 350-550°C; for example, it can be 350°C, 380°C, 400°C, 420°C, 450°C, 480°C, 500°C, 520°C or 550°C, etc. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0040] In some embodiments of the present invention, the reaction time is 2-8 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0041] In a fifth aspect, the present invention provides a catalyst as described in the third aspect or a catalyst prepared by the preparation method as described in the fourth aspect, and its use in catalyzing the pyrolysis of polystyrene.
[0042] In a sixth aspect, the present invention provides a method for converting polystyrene into styrene, the method comprising the steps of:
[0043] The catalyst described in the third aspect or the catalyst prepared by the preparation method described in the fourth aspect, polystyrene and an organic solvent are mixed, and heated to react in an inert atmosphere to thermally decompose the polystyrene to generate styrene.
[0044] The present invention innovatively carries out the thermal decomposition reaction of polystyrene in an organic solvent system, and with the catalyst of the present invention, not only the reaction temperature is reduced, but also the reaction efficiency and the selectivity of styrene are improved.
[0045] In some embodiments of the present invention, the organic solvent is acetonitrile.
[0046] In some embodiments of the present invention, the reaction temperature is 285-295° C., for example, 285° C., 286° C., 287° C., 288° C., 289° C., 290° C., 291° C., 292° C., 293° C., 294° C. or 295° C., etc.; preferably 288-292° C., more preferably 290° C. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0047] In some embodiments of the present invention, the reaction time is 4-16 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 10 hours, 12 hours, 13 hours, 15 hours or 16 hours, etc.; preferably 4-8 hours, more preferably 4 hours. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0048] In some embodiments of the present invention, the mass ratio of the catalyst to the polystyrene is 0.5-2:1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The catalyst provided by the present invention can catalyze the thermal decomposition of polystyrene under relatively mild conditions, so that it can be efficiently and highly selectively converted into styrene; the catalyst is easy to regenerate, has good cycle stability, and is conducive to repeated use; and it is universally applicable in the recycling of commercial waste polystyrene plastics and polystyrene mixed plastics.
[0051] The method for converting polystyrene into styrene provided by the present invention innovatively performs a thermal decomposition reaction of polystyrene in an organic solvent system (especially acetonitrile), and in combination with the catalyst of the present invention, not only the reaction temperature is reduced, but also the reaction efficiency and the selectivity of styrene are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1A TEM image and HRTEM image of the Ni-Beta catalyst provided in Example 1 of the present invention;
[0053] Figure 1B The energy spectrum distribution diagram of the elements in the Ni-Beta catalyst provided in Example 1 of the present invention;
[0054] Figure 1C XRD diagram of the Ni-Beta catalyst and the H-Beta molecular sieve used in Example 1 of the present invention;
[0055] Figure 1D A graph showing the physical adsorption of nitrogen by the Ni-Beta catalyst and the H-Beta molecular sieve used in Example 1 of the present invention;
[0056] Figure 1E The pore size distribution diagram of the Ni-Beta catalyst and the H-Beta molecular sieve used in Example 1 of the present invention;
[0057] Figure 2A NH3-TPD curve diagram of the Ni-Beta catalyst and the H-Beta molecular sieve used in Example 1 of the present invention;
[0058] Figure 2B The pyridine infrared spectra of the Ni-Beta catalyst and the H-Beta molecular sieve provided in Example 1 of the present invention;
[0059] Figure 3A The catalytic pyrolysis effect of H-Beta molecular sieve on polystyrene when using different organic solvents;
[0060] Figure 3B This is a diagram showing the catalytic pyrolysis effect of molecular sieves with different topological structures on polystyrene;
[0061] Figure 4A The catalytic pyrolysis effect of H-Beta molecular sieve on polystyrene at different reaction temperatures;
[0062] Figure 4B The catalytic pyrolysis effect of H-Beta molecular sieve on polystyrene at different reaction times;
[0063] Figure 5A This is a diagram showing the catalytic pyrolysis effect of catalysts with different metal elements on polystyrene;
[0064] Figure 5B This is a diagram showing the catalytic pyrolysis effect of Ni-Beta catalysts with different metal element loadings on polystyrene;
[0065] Fig. 6A This is a diagram showing the catalytic pyrolysis effect of the Ni-Beta catalyst provided in Example 1 of the present invention on polystyrene at different cycle times;
[0066] Figure 6B This is a diagram showing the catalytic pyrolysis effect of the Ni-Beta catalyst provided in Example 1 of the present invention on different commercial polystyrenes;
[0067] Fig. 7A This is a diagram showing the catalytic pyrolysis effect of the Ni-Beta catalyst provided in Example 1 of the present invention on polystyrene in different mixed plastics;
[0068] Figure 7B The solution obtained by catalyzing the thermal decomposition of polystyrene by the Ni-Beta catalyst provided in Example 1 of the present invention in an amplified system 1 H-NMR spectrum. DETAILED DESCRIPTION
[0069] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0070] In the embodiments of the present invention, the sources of some materials are as follows:
[0071] SAPO-34 molecular sieve: Si / Al molar ratio = 0.25:1, Nankai Catalyst Plant;
[0072] USY molecular sieve: Si / Al molar ratio = 2.5:1, Nankai Catalyst Plant;
[0073] ZSM-5 molecular sieve: Si / Al molar ratio = 12.5:1, Nankai Catalyst Plant;
[0074] H-Beta molecular sieve: Si / Al molar ratio = 12.5:1, 15:1, 30:1, Nankai Catalyst Plant.
[0075] Example 1
[0076] This embodiment provides a catalyst, and the preparation method thereof is as follows:
[0077] (1) adding nickel nitrate aqueous solution (100 mg / mL) dropwise onto H-Beta molecular sieve (Si / Al molar ratio = 12.5:1), controlling the raw material ratio so that the mass content of Ni in the catalyst is 0.2%, stirring until the surface is dry, drying in an oven at 120° C. for 12 h, and then calcining in a muffle furnace at 550° C. for 6 h in an air environment, and cooling to room temperature to obtain a catalyst precursor;
[0078] (2) The catalyst precursor is reduced at 450° C. for 2 h under a H 2 atmosphere, cooled to room temperature, and then ground and dried to obtain a catalyst (named Ni-Beta catalyst).
[0079] Embodiments 2 to 4
[0080] Examples 2 to 4 provide a catalyst respectively, which differs from Example 1 only in that the mass contents of Ni in the catalyst are 0.1%, 0.8% and 1.5% respectively.
[0081] Embodiments 5 to 8
[0082] Examples 5 to 8 respectively provide a catalyst, which differs from Example 1 only in that nickel nitrate is replaced by iron nitrate, copper nitrate, zinc nitrate, and cobalt nitrate, respectively, to prepare Fe-Beta catalyst, Cu-Beta catalyst, Zn-Beta catalyst, and Co-Beta catalyst, respectively, in which the mass content of transition metal elements is 0.2%.
[0083] Examples 9 to 14
[0084] Examples 9 to 14 respectively provide a catalyst, which differs from Example 1 only in that the H-Beta molecular sieve (Si / Al molar ratio = 12.5:1) is replaced by SAPO-34 molecular sieve (Si / Al molar ratio = 0.25:1), USY molecular sieve (Si / Al molar ratio = 2.5:1), ZSM-5 molecular sieve (Si / Al molar ratio = 12.5:1), H-Beta molecular sieve (Si / Al molar ratio = 15:1), and H-Beta molecular sieve (Si / Al molar ratio = 30:1), respectively, to prepare Ni-SAPO-34 catalyst, Ni-USY catalyst, Ni-ZSM-5 catalyst, Ni-Beta catalyst (Si / Al molar ratio = 15:1), and Ni-Beta catalyst (Si / Al molar ratio = 30:1), respectively.
[0085] Characterization of physical and chemical properties
[0086] 1. The morphology of the Ni-Beta catalyst provided in Example 1 was characterized by transmission electron microscopy (TEM) and high magnification transmission electron microscopy (HRTEM). The results are as follows: Figure 1A As shown in Figure 1, Figure a is a TEM image, and Figure b is a HRTEM image.
[0087] from Figure 1A It can be seen that the Ni element is evenly dispersed in the form of atoms on the Beta molecular sieve.
[0088] 2. The element distribution of the Ni-Beta catalyst provided in Example 1 was tested using a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM). The results are as follows: Figure 1B shown.
[0089] from Figure 1B It can be seen that the loaded Ni metal is evenly dispersed on the molecular sieve carrier without obvious agglomeration and formation of large nanoparticles.
[0090] 3. The Ni-Beta catalyst and the H-Beta molecular sieve provided in Example 1 were tested by X-ray diffractometer to obtain an X-ray diffraction spectrum (XRD) diagram, as shown in FIG. Figure 1C shown.
[0091] from Figure 1C It can be seen that the loading of Ni metal does not affect the topological structure of the Beta molecular sieve carrier itself. At the same time, no obvious metallic nickel diffraction peak is found in the XRD spectrum, which preliminarily indicates that the obtained metallic nickel species is of smaller particle size.
[0092] 4. The specific surface area and pore size distribution of the Ni-Beta catalyst and the H-Beta molecular sieve provided in Example 1 were tested by nitrogen physical adsorption method to obtain a nitrogen physical adsorption curve and a pore size distribution diagram, respectively. Figure 1D , Figure 1E shown.
[0093] from Figure 1D and Figure 1E It can be seen that the Ni-Beta catalyst provided in Example 1 has a higher specific surface area and an obvious microporous structure, indicating that the microporous structure of the Beta molecular sieve is not changed after loading Ni.
[0094] 5. The Ni-Beta catalyst and the H-Beta molecular sieve provided in Example 1 were tested by ammonia-programmed temperature desorption (NH3-TPD) to obtain an NH3-TPD curve, as shown in FIG. Figure 2A shown.
[0095] from Figure 2A It can be seen that the loading of Ni has little effect on the weak acid density of the catalyst. However, the desorption peak temperature of the weak acid moves to the low temperature region after loading Ni, which indicates that the weak acid strength of the catalyst is reduced.
[0096] 6. The Ni-Beta catalyst and the H-Beta molecular sieve provided in Example 1 were tested by pyridine infrared spectroscopy (Py FT-IR) to obtain a pyridine infrared spectrum, as shown in FIG. Figure 2B shown.
[0097] from Figure 2B It can be seen that Ni-Beta shows more Lewis acid / Acid ratio, indicating that the loaded Ni metal will affect the distribution and number of acid sites of the molecular sieve.
[0098] Catalytic performance test
[0099] 1. Effect of different solvents on catalytic performance
[0100] Experimental method: 200 mg polystyrene (purchased from Acros, M w =260000), 30 mL of an organic solvent (cyclohexane, toluene, tetrahydrofuran, chlorobenzene, mesitylene, acetonitrile) was used as a reaction solvent, and then 200 mg of H-Beta molecular sieves (Si / Al molar ratio = 12.5:1) was added, and the mixture was heated to 290°C under an Ar atmosphere, and reacted for 4 hours to obtain a styrene solution.
[0101] By gas chromatography, mass spectrometry and 1The reaction system was qualitatively and quantitatively analyzed by H-NMR to obtain the conversion rate of polystyrene and the selectivity of each decomposition product (including styrene, ethylbenzene, methylstyrene, isopropylbenzene, toluene, and dimer).
[0102] The yield of styrene when using different organic solvents is as follows Figure 3A As shown in the figure, it can be seen that the yield of styrene when acetonitrile is used as the reaction solvent is much higher than the yield of styrene when other organic solvents are used.
[0103] 2. Effect of different molecular sieve types on catalytic performance
[0104] Experimental method: 200 mg polystyrene (purchased from Acros, M w =260000), 30mL acetonitrile as the reaction solvent, then add 200mg molecular sieve (SAPO-34, USY, ZSM-5, H-Beta (Si / Al molar ratio = 12.5:1)) or catalyst (catalyst provided in Example 1 and Examples 9 to 14), heat to 290°C under Ar gas atmosphere, react for 4 hours, and obtain acetonitrile solution of styrene. The conversion rate of polystyrene and the selectivity of each decomposition product (including styrene, ethylbenzene, methylstyrene, isopropylbenzene, toluene, dimer) are tested, and the results are as follows: Figure 3B As shown, the column represents selectivity, the column height represents the selectivity value, the point represents the conversion rate, and the number after the molecular sieve and catalyst name represents the Si / Al molar ratio.
[0105] from Figure 3B It can be seen that compared with H-Beta molecular sieve (Si / Al molar ratio = 12.5:1), the polystyrene conversion rate of Ni-Beta catalyst (Si / Al molar ratio = 12.5:1) under the same conditions increased from 75% to 99%, and the styrene selectivity did not change significantly (about 87%). Compared with catalysts using other molecular sieves, Ni-Beta catalyst (Si / Al molar ratio = 12.5:1) has the best catalytic performance. And the catalytic activity of Ni-Beta catalyst decreases with the increase of Si / Al molar ratio.
[0106] 3. Effect of different reaction temperatures on catalytic performance
[0107] Experimental method: 200 mg polystyrene (purchased from Acros, M w=260000), 30mL acetonitrile as the reaction solvent, then add 200mg H-Beta molecular sieve (Si / Al molar ratio = 12.5:1), heat to 270-300°C under Ar gas atmosphere, react for 4 hours, and obtain acetonitrile solution of styrene. The conversion rate of polystyrene and the selectivity of styrene are tested. The results are as follows Figure 4A As shown in Figure 2. Among them, red corresponds to conversion rate and blue corresponds to selectivity.
[0108] from Figure 4A It can be seen that in the range of 270-300℃, the polystyrene conversion rate increases with the increase of reaction temperature; the styrene selectivity first increases and then decreases with the increase of reaction temperature, and the styrene selectivity is the highest at 290℃.
[0109] 4. Effect of different reaction times on catalytic performance
[0110] Experimental method: 200 mg polystyrene (purchased from Acros, M w =260000), 30 mL of acetonitrile as the reaction solvent, then add 200 mg of H-Beta molecular sieve (Si / Al molar ratio = 12.5:1), heat to 290°C under Ar gas atmosphere, react for 1-16 hours, and obtain acetonitrile solution of styrene. The conversion rate of polystyrene and the selectivity of styrene are tested. The results are as follows Figure 4B As shown in Figure 2. Among them, red corresponds to conversion rate and blue corresponds to selectivity.
[0111] from Figure 4B It can be seen that the polystyrene conversion rate gradually increases with the extension of reaction time, reaching about 75% at 4h; the styrene selectivity fluctuates within a certain range with the reaction time, and when the reaction time exceeds 4h, the styrene selectivity decreases. Figure 4A and Figure 4B It can be seen that the comprehensive catalytic effect is best when the reaction temperature is 290°C and the reaction time is 4h.
[0112] 5. Effects of different metal elements on catalytic performance
[0113] Experimental method: 200 mg polystyrene (purchased from Acros, M w =260000), 30 mL of acetonitrile as the reaction solvent, then 200 mg of catalyst (the catalyst provided in Example 1 and Examples 5 to 8) was added, heated to 290°C under an Ar atmosphere, and reacted for 4 hours to obtain an acetonitrile solution of styrene. The conversion rate of polystyrene and the selectivity of each decomposition product (including styrene, ethylbenzene, methylstyrene, isopropylbenzene, toluene, and dimer) were tested, and the results were as follows: Figure 5AAs shown, the column represents selectivity, the column height represents the selectivity value, and the point represents the conversion rate.
[0114] from Figure 5A It can be seen that there is no significant difference in the styrene selectivity of each catalyst; the polystyrene conversion rates of Cu-Beta catalyst, Zn-Beta catalyst, Co-Beta catalyst and Ni-Beta catalyst are significantly higher than those of Fe-Beta catalyst; Co-Beta catalyst and Ni-Beta catalyst have the best catalytic performance, with polystyrene conversion rates of about 99% and styrene selectivity of about 87%.
[0115] 6. Effect of different metal element loadings on catalytic performance
[0116] Experimental method: 200 mg polystyrene (purchased from Acros, M w =260000), 30 mL of acetonitrile as the reaction solvent, then 200 mg of catalyst (the catalyst provided in Examples 1 to 4) was added, heated to 290°C under an Ar atmosphere, and reacted for 4 hours to obtain an acetonitrile solution of styrene. The conversion rate of polystyrene and the selectivity of each decomposition product (including styrene, ethylbenzene, methylstyrene, isopropylbenzene, toluene, and dimer) were tested, and the results were as follows: Figure 5B As shown, the column represents selectivity, the column height represents the selectivity value, and the point represents the conversion rate.
[0117] from Figure 5B It can be seen that when the Ni loading is in the range of 0.1-1.5%, the polystyrene conversion rate increases first and then decreases with the increase of Ni loading, and the polystyrene conversion rate is the highest when the Ni loading is 0.2%; the styrene selectivity changes little with the Ni loading. This shows that the catalytic performance of the catalyst is best when the Ni loading is 0.2%.
[0118] 7. Cyclic stability of catalyst
[0119] Experimental method: 200 mg polystyrene (purchased from Acros, M w =260000), 30 mL of acetonitrile as the reaction solvent, then 200 mg of the catalyst provided in Example 1 was added, and the mixture was heated to 290°C under an Ar atmosphere for 4 hours to obtain an acetonitrile solution of styrene. After the reaction, the catalyst was separated by centrifugation, calcined in a muffle furnace at 550°C for 6 hours under an air environment, and then reduced at 450°C for 2 hours under a H2 atmosphere to regenerate the catalyst and use it again to catalyze the thermal decomposition of polystyrene. The above experiment was repeated to test the conversion rate of polystyrene and the selectivity of styrene in each cycle. The results are shown in FIG. Fig. 6A As shown in Figure 2. Among them, red corresponds to conversion rate and blue corresponds to selectivity.
[0120] from Fig. 6A It can be seen that after 5 cycles, the polystyrene conversion rate and styrene selectivity did not change significantly, indicating that the catalyst provided by the present invention has good cycle stability.
[0121] 8. Catalytic effects of different polystyrene plastics
[0122] Experimental method: Add 200 mg of polystyrene (disposable cups, coffee cup lids, foam, doll stuffing) and 30 mL of acetonitrile as the reaction solvent into the reactor, then add 200 mg of the catalyst provided in Example 1, heat to 290°C under Ar gas atmosphere, react for 4 hours, and obtain acetonitrile solution of styrene. Test the conversion rate of polystyrene and the selectivity of styrene. The results are as follows: Figure 6B shown.
[0123] from Figure 6B It can be seen that the catalyst provided by the present invention has a good catalytic pyrolysis effect on different commercial polystyrenes.
[0124] 9. Catalytic effect of mixed plastics of different types
[0125] Experimental method: Add 200 mg of mixed plastics (PS+2% PET, PS+2% PP, PS+2% PVC, PS+2% PE) and 30 mL of acetonitrile as the reaction solvent into the reactor, then add 500 mg of the catalyst provided in Example 1, heat to 290°C under Ar gas atmosphere, react for 12 hours, and obtain acetonitrile solution of styrene. Test the conversion rate of polystyrene and the selectivity of styrene. The results are as follows: Fig. 7A shown.
[0126] from Fig. 7A It can be seen that although the mixing of other plastics into polystyrene will lead to a decrease in the catalytic effect of the catalyst of the present invention, the conversion rate of polystyrene can still reach more than 90%, and the selectivity of styrene can still reach more than 67%.
[0127] 10. Effect of the amplification system on catalytic performance
[0128] Experimental method: 4 g of polystyrene and 50 mL of acetonitrile as the reaction solvent were added to the reactor, and then 2 g of the catalyst provided in Example 1 was added. The mixture was heated to 290°C under an Ar atmosphere and reacted for 12 hours to obtain a styrene acetonitrile solution. The NMR hydrogen spectrum of the solution was tested. The results were as follows: Figure 7B shown.
[0129] from Figure 7B It can be seen that the styrene product in the obtained solution is relatively pure, indicating that a high styrene selectivity can still be maintained after the system is enlarged.
[0130] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A catalyst precursor, characterized in that: The catalyst precursor includes a molecular sieve and a transition metal element supported in the molecular sieve; The molecular sieve is H-Beta molecular sieve and / or ZSM-5 molecular sieve; The transition metal element is selected from one or more of Cu, Zn, Co and Ni, and the transition metal element exists in the form of oxide.
2. The catalyst precursor according to claim 1, characterized in that The loading amount of the transition metal element in the catalyst precursor is 0.1-1wt%, preferably 0.1-0.8wt%, more preferably 0.2wt%; Preferably, the transition metal element is Co and / or Ni; Preferably, the molecular sieve is H-Beta molecular sieve; Preferably, the molar ratio of Si to Al in the molecular sieve is 10-13:
1.
3. A method for preparing a catalyst precursor as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: The aqueous solution of the transition metal salt is mixed with the molecular sieve, dried, and then calcined in an oxygen-containing atmosphere to decompose the transition metal salt to form oxides, thereby obtaining the catalyst precursor.
4. The preparation method according to claim 3, characterized in that: The transition metal salt is a nitrate of a transition metal; Preferably, the concentration of the transition metal element in the aqueous solution of the transition metal salt is 0.5-1 mol / L; Preferably, the mixing method is: dropping the aqueous solution of the transition metal salt onto the molecular sieve and stirring until the surface is dry; or, immersing the molecular sieve in the aqueous solution of the transition metal salt for a period of time and separating the solid; Preferably, the drying method is: drying at 100-120°C; Preferably, the calcination temperature is 450-650° C., and the calcination time is 4-8 hours.
5. A catalyst, characterized in that The catalyst comprises a molecular sieve and a transition metal element supported in the molecular sieve; The molecular sieve is H-Beta molecular sieve and / or ZSM-5 molecular sieve; The transition metal element is selected from one or more of Cu, Zn, Co and Ni, and the transition metal element exists in the form of a metal element.
6. The catalyst according to claim 5, characterized in that The loading amount of the transition metal element in the catalyst is 0.1-1wt%, preferably 0.1-0.8wt%, more preferably 0.2wt%; Preferably, the transition metal element is Co and / or Ni; Preferably, the molecular sieve is H-Beta molecular sieve; Preferably, the molar ratio of Si to Al in the molecular sieve is 10-13:
1.
7. A method for preparing the catalyst according to claim 5 or 6, characterized in that: The preparation method comprises the following steps: The catalyst precursor according to claim 1 or 2, or the catalyst precursor prepared by the preparation method according to claim 3 or 4, is heated in a reducing atmosphere to reduce the oxide of the transition metal element in the catalyst precursor to a metal element, thereby obtaining the catalyst.
8. The preparation method according to claim 7, characterized in that: The reducing atmosphere is a hydrogen atmosphere; Preferably, the reaction temperature is 350-550° C., and the reaction time is 2-8 h.
9. Use of the catalyst according to claim 5 or 6 or the catalyst prepared by the preparation method according to claim 7 or 8 in catalyzing the thermal decomposition of polystyrene.
10. A method for converting polystyrene into styrene, characterized in that The method comprises the following steps: Mixing the catalyst according to claim 5 or 6 or the catalyst prepared by the preparation method according to claim 7 or 8, polystyrene and an organic solvent, and heating them in an inert atmosphere to react, so that the polystyrene is thermally decomposed to generate styrene; Preferably, the organic solvent is acetonitrile; Preferably, the reaction temperature is 285-295°C, preferably 288-292°C, more preferably 290°C; Preferably, the reaction time is 4-16h, preferably 4-8h, more preferably 4h; Preferably, the mass ratio of the catalyst to the polystyrene is 0.5-2:1.
Citation Information
Patent Citations
Catalyst for producing high-value-added bio-oil and preparation method of catalyst
CN106861749A
Preparation method of lignin-based phenolic aqueous phase reforming hydrogen production catalyst
CN108212200A
Preparation method and application of tar cracking catalyst
CN114082439A
Application of nickel-based Beta zeolite catalyst in preparation of synthesis gas by methane dry reforming
CN115722260A
Lamellar morphology heteroatom zeolite molecular sieve catalyst for catalyzing polyolefin plastic cracking
CN116747898A